Pemanfaatan Modal Dedi Sitorus Sebagai Pendatang Baru PILEG Tahun 2019 DAPIL Kaltara - Ansar Ansar; Muradi Muradi; Ferry Kurnia Rizkiansyah (Universitas Medan Area, 2022)
This paper aims to determine the capital utilization of a newcomer candidate who wins in an electoral district that has just been expanded, the problem is focused on how aspects of social capital, political capital and economic capital of a newcomer actor. In order to approach this problem, the theoretical reference from Bordieu (1992) and Maridjan (2006) data collected through field data and documentation is used and analyzed qualitatively. This study concludes that Dedi Sitorus's victory was due to having more than one capital. There are several important fundamental considerations such as: first, Dedi Sitorus' social capital has a Social Network in the Nunukan community, Second, Dedi Sitorus' political capital has support from parties starting from the central level and also the DPC administrator at the Nunukan Regency level and also the support from regional authorities and also figures Local Politics, Third Economic Capital Dedi Sitorus has very large finances so he does not need donors to carry out his campaign and has the ability to rent air transportation to carry out mobility in campaigns. With the accumulation of all the capital owned, Dedi Sitorus can take advantage and use the moment well so that he gets a significant vote in the 2019 legislative elections.